The relationship between building design and maintenance operation of state mosque / Muhammad Amirul Aizat Abdullah - Abdullah, Muhammad Amirul Aizat (Faculty of Architecture, Planning and Surveying, 2015)
Building Maintenance is an important factor to maintain building performance and quality. Faulty in building design can lead to many maintenance problem in the building and lead to building defects. The aimed for this research is aimed to establish the criteria of faulty building design that affect maintenance operation of state mosque. The methodology used in this study was based on semi-structure interview and fieldwork to determine faulty in building design and identify the factor in faulty building design that affect maintenance operation. . Three (3) case studies at Tuanku Mizan Zainal Abidin Mosque, Putrajaya, Sultan Salahuddin Abdul Aziz Mosque, Selangor and Malacca Straits Mosque, Melaka have been selected to do this research. Each of the respondents at the building has been involved in maintenance operation work which is Facility Manager and Head of Building Management. This research resulted that three main factors of building design that affect maintenance operation which is defect in design, defect in material and defect in maintenance. The factors can lead to increase of maintenance budget in the building hence it can affect the quality and performance of the building. Building maintenance is important for every building and consideration of maintenance operation work in building design need to be emphasizing to prevent and prolong building lifetime and performance.